2018
DOI: 10.3390/ijms19041094
|View full text |Cite
|
Sign up to set email alerts
|

Remote Ischemic Preconditioning Does Not Affect the Release of Humoral Factors in Propofol-Anesthetized Cardiac Surgery Patients: A Secondary Analysis of the RIPHeart Study

Abstract: In contrast to several smaller studies, which demonstrate that remote ischemic preconditioning (RIPC) reduces myocardial injury in patients that undergo cardiovascular surgery, the RIPHeart study failed to demonstrate beneficial effects of troponin release and clinical outcome in propofol-anesthetized cardiac surgery patients. Therefore, we addressed the potential biochemical mechanisms triggered by RIPC. This is a predefined prospective sub-analysis of the randomized and controlled RIPHeart study in cardiac s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 42 publications
0
13
0
1
Order By: Relevance
“…For example, a study found that the serum level of macrophage migration inhibitory factor was increased, whereas no difference was found in IL-6, IL-8, and IL-10 serum levels between the RIPC group and a control group in patients undergoing cardiac surgery. 31 Another study reported increased blood levels of TNF-α, IL-6, IL-8, and IL-10 in 5 healthy volunteers after RIPC. 32 TNF-α and IL-6 play major roles in initiating and amplifying the postischemic inflammatory response, whereas IL-10 is mainly an anti-inflammatory factor.…”
Section: Discussionmentioning
confidence: 99%
“…For example, a study found that the serum level of macrophage migration inhibitory factor was increased, whereas no difference was found in IL-6, IL-8, and IL-10 serum levels between the RIPC group and a control group in patients undergoing cardiac surgery. 31 Another study reported increased blood levels of TNF-α, IL-6, IL-8, and IL-10 in 5 healthy volunteers after RIPC. 32 TNF-α and IL-6 play major roles in initiating and amplifying the postischemic inflammatory response, whereas IL-10 is mainly an anti-inflammatory factor.…”
Section: Discussionmentioning
confidence: 99%
“…Contrary to the findings in animal models, the majority of recent randomised control clinical trials have been unable to demonstrate a clear effect of RIC on pro-inflammatory cytokine release (Table .2 ) [ 37 , 39 , 105 , 106 , 108 , 149 , 158 ]. However, to date, cytokines have predominantly been measured in small studies only (less than 100 participants).…”
Section: Cytokines In Myocardial Infarction and Infectionmentioning
confidence: 86%
“…27 RIPC has also been found to modulate the inflammatory response. 28 Yet there was no effect of RIPC seen on inflammatory mediators either in propofol anaesthetised 29 or sevoflurane anaesthetised cardiac surgery patients. 30 There are several limitations to the present study.…”
Section: Subgroup Analysismentioning
confidence: 96%